Effect of temperature on permeability of mudstone subjected to triaxial stresses and its application - Jieqing Yu; Fuke Dong; Yu Zhou; Xingyan Wang; Liang Zhang; Hailong Su (Scientific Reports)
Abstract In order to prevent leakage of pyrolysed oil and gas and the release of contaminants from the top and bottom strata, it is essential to carry out a comprehensive study of the seepage behaviour of these strata under high temperature triaxial stress conditions. The findings of this study will contribute to the development of effective strategies for the containment and integrity monitoring of subsurface reservoirs and storage environments. Mudstone, serving as both the upper and lower strata, offers an effective barrier due to its inherently low permeability. In order to explore the change rule of mudstone sealing performance under high temperature triaxial stress, an air-heated low permeability rock mass air permeability measurement system is used to measure the ground stress buried 500 m deep and the temperature variation characteristics of mudstone permeability on the roof and floor of Jimsar oil shale in Xinjiang under 100 °C. It was found that the permeability of stressed mudstone decreased with the temperature rising up to 100 °C. The primary factor influencing the outcome was the thermal expansion of the mudstone. The magnitude of the drop value was contingent upon the triaxial stresses that could potentially be induced by the application of significant tensile forces, resulting in a relatively minor drop value. The average hydraulic radius of pore in the mudstone was also calculated, which also exhibited continuous reduction as heating up to 100 °C and the degree of reduction could reach 68%. The capacity, that prevent oil & gas and contaminant from moving cross strata as a barrier, would be strengthened when the mudstone strata from roof and floor experienced the temperature low than 100 °C. The barrier performance of mudstone as a pollutant migration barrier layer to gas pollutant migration during in-situ heat injection mining of oil shale was further evaluated.